2021
DOI: 10.1155/2021/1438837
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Pattern of CALCA and CALCB in Extremely Premature Infants with Monochorionic Triplets after Single‐Embryo Transfer

Abstract: Compared with full-term peers, premature infants are more likely to suffer from neonatal diseases and death. Variations in DNA methylation may affect these pathological processes. Calcitonin gene-related peptide (CGRP) plays a complex and diversified role in reproduction and chronic inflammation, and participates in the functional maintenance of vascular adaptation and trophoblast cells during pregnancy. Here, premature live births with single-chorionic triple embryos after single-embryo transfer were used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…It is to be noted that variations of DNA methylation in samples from the placental and umbilical cord tissues, saliva and cord blood of new birth weight neonates have been claimed to mediate perinatal programming of non-communicable diseases later in life. Genome-wide DNA methylation studies have revealed association between differentially methylated DNA and neurodevelopmental impairments and compromised immune functions of the neonates [40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…It is to be noted that variations of DNA methylation in samples from the placental and umbilical cord tissues, saliva and cord blood of new birth weight neonates have been claimed to mediate perinatal programming of non-communicable diseases later in life. Genome-wide DNA methylation studies have revealed association between differentially methylated DNA and neurodevelopmental impairments and compromised immune functions of the neonates [40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…It is also to be noted that variations of DNA methylation in samples from the placental and umbilical cord tissues, saliva, and cord blood of low-birthweight neonates have been claimed to mediate perinatal programming of several diseases later in life. Genome-wide methylation studies have revealed an association between differentially methylated DNA, neurodevelopmental impairments, and compromised immune functions in neonates [72][73][74][75].…”
Section: Dna Methylationmentioning
confidence: 99%